The relationship between teachers’ emotional intelligence and teaching for creativity: The mediating role of working engagement - Huili Su; Jingwei Zhang; Mingyue Xie; Ming Zhao (Frontiers in Psychology, 2022)
Teaching for creativity (TfC) has received increasing attention as an important way to cultivate students’ creative thinking and behaviors. The purpose of this study is to examine the mediating role of teachers’ work engagement (WE) on the relationship between their emotional intelligence (EI) and teaching for creativity. The study is a cross-sectional design. The sample of the study is 3,307 secondary school English teachers working in Jilin Province, China. The findings show that the teachers’ perceptions of emotional intelligence, work engagement and teaching for creativity are relatively high. The findings confirm the hypotheses. The results of structural equation modeling and bootstrapping show that teachers’ emotional intelligence is positively correlated with work engagement and teaching for creativity, and teachers’ work engagement mediates the relationship between emotional intelligence and teaching for creativity.